Pengaruh GPM, Ukuran Perusahaan Terhadap Nilai Perusahaan Sektor Teknologi Di Bursa Efek Indonesia Periode 2021 – 2024: The Effect of GPM and Company Size on the Value of Technology Companies on the Indonesia Stock Exchange for the Period 2021–2024 - Fina Saindri; Tri Lestari (CV Warnak Johanna Nusantara, 2025)
The rapid development of Indonesia’s technology sector has intensified competition, making firm value increasingly dependent on profitability and structural characteristics. While profitability and firm size are often viewed as key drivers of value, prior findings in emerging markets remain inconclusive. This study investigates the influence of Gross Profit Margin and Firm Size on the value of technology companies listed on the Indonesia Stock Exchange from 2021 to 2024. Using a quantitative approach, purposive sampling identified twenty-six firms that consistently published financial reports during the observation period. Quantile regression was employed to overcome the limitations of classical regression and to capture variations across different firm value levels. The results indicate that profitability plays a stronger role in enhancing firm value among companies with medium to high market positions, whereas firm size tends to exert a negative effect on firms with relatively lower valuations. These findings suggest that market participants in the Indonesian technology sector respond more to profitability than to scale. The novelty of this research lies in applying quantile regression within the Indonesian technology sector, offering a nuanced perspective on heterogeneous effects often overlooked in conventional analyses